The extent to which student activities contribute to the development of some physical skills among the students of the intermediate school - Al-Anzi, Abdullah bin Ahmed (Journal of Educational and Psychological Sciences, 2019)
The aim of the research is to identify the role of student activities in developing some aspects of mobility among students in Al Hudaybiyah intermediate school. To achieve this goal, the researcher used the analytical descriptive method. The researcher also used a set of study tools, including a rectometer, a medical balance and a stopwatch, as well as a set of tests that develop the physical aspects of students. The study sample consisted of (60) students from Al Hudaybiyah Middle School in Hafr Al Batin Governorate in Saudi Arabia. They were divided into two groups, one experimental and the other 30 students. The program was implemented in the first semester of 1439/1440 E. The results of the study showed the following:• There are statistically significant differences between the mean scores of the tribal and remote measurements of the control group in favor of dimension measurements in some physical aspects under consideration.• There are statistically significant differences between the mean scores of the tribal and remote measurements of the experimental group in favor of dimension measurements in some physical aspects in question.• There are statistically significant differences between the averages of the two dimensional measurements of the control and experimental groups in favor of the post-measurement of the experimental group in some physical aspects.• The effectiveness of the proposed program for the development of physical skills for middle school students.The study recommended focusing on student activities in the intermediate stage and the need to implement many programs of activities that help to improve the physical fitness of students.
Keywords: student activities; physical skills; the intermediate stage